Computer Vision Based Advanced Cloud Security Using Face Recognition - Akshat Sharma, S Priya, Rohith Reddy Chinta, Ria Nair (International Journal of Advanced Science and Technology, 2020)
The detection of face from images plays an important part in Computer vision as well as Forensic Science. Various models ranging from computational to mathematical have been proposed for differentiating faces which includes Scale Invariant Feature transform (SIFT) and Dominant Rotated Local Binary Pattern (DRLBP). This paper proposes a different method of classifying the human face using Haar. It starts with preprocessing of the image and then extracting the specific features of the face. The detection of human faces is done using Haar and recognition is done by a classifier. Keywords : Computer Vision, Forensic Science, Haar, Classifier.